Digital Literacy and Its Relationship to Early Childhood Behavior in PAUD - Fatimah (Kanal: Jurnal Ilmu Komunikasi, 2020)
This study aims to determine the relationship between digital literacy and early childhood behavior (PAUD) in PAUD . This research is an analytical quantitative type. The research design used was a study. The population that is the object of this study is all students in PAUD with a population of 100 people. The sample in this study was based on the calculation of the formula to 80 people. Sampling is carried out with the principle of pro-proportional sampling, where samples will be taken according to proportions. Based on the results of the study there is a relationship between digital literacy variables and student behavior in PAUD , P = 0.021. This can be known by the significance value (P) 0.021 <0.05. The conclusion from the results of the study conducted to 80 respondents consisting of children aged 3-5 years. Having a conclusion about the relationship of digital literacy in early childhood and how it relates to early childhood behavior in PAUD . 55.0% of respondents have good behavior with this digital literacy. The remaining 45.0% percent have bad behavior due to this digital literacy. Suggestions are needed the role of parents and PAUD in assisting and educating children on the benefits and dangers of using gadgets / other electronic equipment.